DPP4 and ACE2 in Diabetes and COVID-19: Therapeutic Targets for Cardiovascular Complications? - Valencia, Inés; Peiró, Concepción; Lorenzo, Óscar; Sánchez-Ferrer, Carlos F.; Eckel, Jürgen; Romacho, Tania (Frontiers in Pharmacology, 2020)
COVID-19 outbreak, caused by severe acute respiratory syndrome (SARS)-CoV-2 coronavirus has become an urgent health and economic challenge. Diabetes is a risk factor for severity and mortality of COVID-19. Recent studies support that COVID-19 has effects beyond the respiratory tract, with vascular complications arising as relevant factors worsening its prognosis, then making patients with previous vascular disease more prone to severity or fatal outcome. Angiotensin-II converting enzime-2 (ACE2) has been proposed as preferred receptor for SARS-CoV-2 host infection, yet specific proteins participating in the virus entry are not fully known. SARS-CoV-2 might use other co-receptor or auxiliary proteins allowing virus infection. In silico experiments proposed that SARS-CoV-2 might bind dipeptiyl peptidase 4 (DPP4/CD26), which was stablished previously as receptor for MERS-CoV. The renin-angiotensin-aldosterone system (RAAS) component ACE2 and DPP4 are proteins upregulated in diabetes. Imbalance of the RAAS and direct effect of soluble DPP4 exert deleterious vascular effects. We hypothesize that diabetic patients might be more affected by COVID-19 due to increased presence ACE2 and DPP4 mediating infection and contributing to a compromised vasculature. Here, we discuss the role of ACE2 and DPP4 as relevant factors linking the risk of SARS-CoV-2 infection and severity of COVID-19 in diabetic patients and present an outlook on therapeutic potential of current drugs targeted against RAAS and DPP4 to treat or prevent COVID-19-derived vascular complications. Diabetes affects more than 400 million people worldwide, thus better understanding of how they are affected by COVID-19 holds an important benefit to fight against this disease with pandemic proportions.